A Unit Plan Based Upon The MI Theory: A theoretical study with an application Inside The Classroom (Journal of the College of Education for Women, 2019)
This research basically gives an introduction about the multiple intelligencetheory and its implication into the classroom. It presents a unit plan based upon theMI theory followed by a report which explains the application of the plan by theresearcher on the first class student of computer department in college of sciences/University of Al-Mustansiryia and the teacher's and the students' reaction to it.The research starts with a short introduction about the MI theory is a greattheory that could help students to learn better in a relaxed learning situation. It ispresented by Howard Gardener first when he published his book "Frames ofMinds" in 1983 in which he describes how the brain has multiple intelligences notonly one general intelligence as it was believed before.He classifies theseintelligences into six or ten intelligences as will be explained later in this research.The next section is a unit plan which is designed in accordance with the MItheory for teaching the simple present and the present perfect tense for the firstclass students in computer department of college of sciences. This plan consists offour activities each involves more than three intelligences which suppose to helpmost of the students in the class to learn better, each using their own intelligence inlearning. In all the activities, the students are supposed to work in groups.Activity number one is teaching the simple present tense by writing adescription of pictures taken from the net using the simple present tense.Activity number two is teaching the present perfect tense by using a gamecalled: "tell us what has happened". The teacher or groups of students do somethingand then the teacher asks the other students to tell what has happened.The third activity is teaching the simple present tense by using songs whichare taken from the net and designed for teaching purposes. These songs arefollowed by a cloze sheet about the song to be filled by the students using thesimple present tense.The fourth activity is teaching the present perfect tense using thequestionnaire. Students ask and answer using the present perfect tense as theteacher gives each group a specific theme to talk about.presents the teacher's reaction to using the MI theory in designing the unitplan and teaching it to the students and the students' reaction to the unit plan with the type of assessments according to the MI theory which is followed by the researcher to assess the students.